The Influence of Consciousness Evolution on the Transformation toward Sustainable Real Estate Development - Panthasen, Tanapon (Journal of Architectural/Planning Research and Studies (JARS), 2018)
The development under the egocentric paradigm has contributed to so many global-crises, in both spiritual and physical dimensions, that the “sustainable development” paradigm had to be announced as a basis of any future resolutions. Such announcement has stimulated lots of results supporting sustainable development in various aspects. However, most of those results have failed to emphasize consciousness evolution although international experts in every area have consented the consciousness evolution is crucial for the time being as sustainable development concepts are so limited, especially in real estate sector. So, this study aims at revealing the influence of consciousness evolution on the quality of real estate development by employing Buddha-Dharma and Integral Theory, developed under integral paradigm, in exploring the transformation towards sustainable real estate development through urban-communities internationally. The findings indicate that the transformation toward integral sustainability occurred, and that the consciousness evolution is the primary factor enabling this occurrence. Therefore, the conclusion reiterates the emergence of sustainable real estate depends on development of all life-dimensions, not just development of social systems such as economics, regulations, and technologies. It is especially crucial to note that only with maturity of consciousness lifted above ego, could human see the holistic realm of the phenomenon, including the advantages and disadvantage of every sciences and everyone. This seeing, in return, would enable human to integrate all advantages in a balance manner, resulting in appropriate approaches to take the world out of the crises, toward balance and sustainability.